The compaction behavior of Magnesium-Expanded Natural Graphite powder mixtures: Tensile strengths of compacted pellets - Guden, Mustafa; Betin, Bahattin Berkan; Heptepe, Cafer Can; Gulec, Efe Bati; Yagci, Yavuz Emre; Figen, Aysel Kanturk; Filiz, Bilge Coskuner (ELSEVIER, 2024)
The effects of Expanded Natural Graphite (ENG) content, powder mixing method and compaction pressure on the tensile strengths of Magnesium AZ91 (9 wt% Al, 1 wt% Zn and 0.2 wt% Mn) + ENG powder mixture pellets were investigated. The tensile strengths of the pellets increased with an increase in the ENG content and compaction pressure and also with the applied powder ball milling. However, the compaction pressures above 500 MPa resulted in shear banding.
Keywords: Magnesium; Expanded Natural Graphite; Compacts; Tensile strength; METAL HYDRIDE COMPOSITES; ALLOY; Materials Science; Physics